2020
DOI: 10.3390/cancers12123820
|View full text |Cite
|
Sign up to set email alerts
|

Circulating IL-13 Is Associated with De Novo Development of HCC in HCV-Infected Patients Responding to Direct-Acting Antivirals

Abstract: Direct-acting antivirals (DAAs) are highly effective in targeting hepatitis C virus (HCV) infections, but the incidence of HCV-related hepatocellular carcinoma (HCC) remains still high. In this study, we investigated a cohort of HCV-infected patients treated with DAAs who were followed up for 4 years after sustained virological response (SVR) achievement. Patients who developed de novo HCC following DAA treatment were compared to matched controls who did not develop HCC. These control patients were selected ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 21 publications
2
11
1
Order By: Relevance
“…Patients who developed de novo HCC following DAA treatment were compared to matched control patients that were selected based on DAA treatment, sex, age, fibrosis status, and platelet counts. As significant differences in IL-13 and IL-4 were observed, before DAA treatment, this study validates the existence of a specific immune-related profile in patients who develop de novo HCC after DAA-induced virus eradication [57].…”
Section: Immunological Biomarkerssupporting
confidence: 80%
“…Patients who developed de novo HCC following DAA treatment were compared to matched control patients that were selected based on DAA treatment, sex, age, fibrosis status, and platelet counts. As significant differences in IL-13 and IL-4 were observed, before DAA treatment, this study validates the existence of a specific immune-related profile in patients who develop de novo HCC after DAA-induced virus eradication [57].…”
Section: Immunological Biomarkerssupporting
confidence: 80%
“…The association of type 2 inflammation with tumorigenesis in humans is not limited to autoimmune disorders but also plays roles in a variety of conditions including infection and autoinflammatory conditions. A recent cohort study found that patients who developed hepatocellular carcinoma despite maintaining a sustained virological response against hepatitis C virus were linked to increased circulating levels of IL13 ( Macek Jilkova et al, 2020 ). These patients were matched to controls who did not develop hepatocellular carcinoma, and IL13 was found to be the only strong factor associated with its development.…”
Section: Type 2 Inflammation May Be a Shared Process Of Tumorigenesis Driven By Autoimmunity And Other Chronic Inflammatory Conditionsmentioning
confidence: 99%
“…A recent study showed that patients with the development of hepatocellular carcinoma (HCC) after DAA therapy have lower sCD137 compared to patients who do not develop HCC [37]. During the follow‐up of 3 months, six patients developed HCC in our cohort.…”
Section: Resultsmentioning
confidence: 93%
“…Activation of CD137 promotes tumoricidal effects in monocytes and T cells [7,64]. Unexpectedly, serum sCD137 levels were low in HCV-infected patients who developed HCC within 4 years after DAA therapy [37]. This difference in sCD137 levels was, however, no longer apparent at 3 months after viral eradication [37].…”
Section: Discussionmentioning
confidence: 99%